PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) BERBANTUAN MEDIA GEO3D BOOK TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS V SD NEGERI WONOYOSO - Sovy Abelia Kumala Sari; Hesti Yunitiara Rizqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model assisted by the Geo3D Book on the creative thinking skills of fifth-grade students at SD Negeri Wonoyoso in learning the topic of three-dimensional geometry. This research was motivated by students' low level of creative thinking skills. The study employed a quantitative approach using a quasi-experimental design with purposive sampling. The research sample consisted of Class VA as the experimental group, which received instruction through the Project-Based Learning (PjBL) model assisted by the Geo3D Book and Class VB as the control group, which received Project-Based Learning (PjBL) without the Geo3D Book. The research instrument was a creative thinking skills test that had been validated and tested for reliability. Data were analyzed using SPSS through prerequisite tests (normality and homogeneity), an independent samples t-test, and simple linear regression analysis. The results of the t-test showed a significance value of 0.005 (< 0.05) with a calculated t value of 2.916, which was greater than the critical t value of 2.000, indicating a significant difference between the two groups. The regression analysis yielded a significance value of 0.000 (< 0.05) with a coefficient of determination (R²) of 0.687, indicating that the use of the Project-Based Learning (PjBL) model assisted by the Geo3D Book contributed 68.7% to the improvement of students' creative thinking skills. Therefore, the Project-Based Learning (PjBL) model assisted by the Geo3D Book was proven to be effective in improving the creative thinking skills of elementary school students.